2020
DOI: 10.1039/d0fo01830a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of protein hydrolysates against their native counterparts in terms of structural and antioxidant properties, and when used as emulsifiers for curcumin nanoemulsions

Abstract: This study investigated the stability and the in vitro digestion of curcumin nanoemulsions stabilized by three protein hydrolysates: peanut protein isolate (PPI), soybean protein isolate (SPI) and whey protein isolate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Thus, higher energy barrier among emulsion droplets insisted, providing more stable emulsion. 4,5 In Table 2, the absolute zeta-potential value of BBPI-EGCG was 30.90 AE 0.26 mV growing from 24.47 AE 0.23 mV of BBPI, and value of BBPI-G-EGCG (29.47 AE 0.61 mV) was also higher than BBPI-G (23.20 AE 0.17 mV). The results indicated that high electrostatic repulsion observed from zeta-potential measurement led to stable emulsion with small mean particle size.…”
Section: Emulsion Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, higher energy barrier among emulsion droplets insisted, providing more stable emulsion. 4,5 In Table 2, the absolute zeta-potential value of BBPI-EGCG was 30.90 AE 0.26 mV growing from 24.47 AE 0.23 mV of BBPI, and value of BBPI-G-EGCG (29.47 AE 0.61 mV) was also higher than BBPI-G (23.20 AE 0.17 mV). The results indicated that high electrostatic repulsion observed from zeta-potential measurement led to stable emulsion with small mean particle size.…”
Section: Emulsion Propertiesmentioning
confidence: 96%
“…), which is able to improve stability of ingredients by reducing the exposure of hydrophobic biological active substance to external factors, such as oxygen and light. 4 In the process of emulsion preparation, the emulsier can form an interface layer to separate the oil-water phase. The densication, thickness, stability and anti-oxidation of the emulsier layer will have an important inuence on the stability of the emulsion and the encapsulated substance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for this might be that Wpi surface was negatively charged; another possible explanation for this was that the charged groups like carboxylic moieties (‐COOH) of Wpi were exposed after reaction. Under the influence of stronger electrostatic repulsion between droplets, forming a stable emulsion because the aggregation and flocculation of droplets was hindered (Jin et al., 2020). Thus, under the same surfactant to oil ratio, the performance of Wpi‐Rha was better than that of Tween 80.…”
Section: Resultsmentioning
confidence: 99%
“…The mean particle size and polydispersity index (PDI) of the nanoemulsions were all volume-based, which was determined using dynamic light scattering (Zetasizer Nano-ZS90, Malvern Instruments, Worcestershire, UK). The ζ-potential of the nanoemulsion system was investigated using electrophoresis (Zetasizer Nano-ZS90, Malvern Instruments, Worcestershire, UK) [ 19 , 20 ]. In order to avoid multiple light scattering effects, the emulsion was diluted (1:100 v/v ) with 10 mmol/L pH = 7.0 phosphate buffer solution (8 g NaCl, 0.2 g KCl, 1.44 g Na 2 HPO 4 , 0.24 g KH 2 PO 4 per liter) and mixed thoroughly.…”
Section: Methodsmentioning
confidence: 99%